2016
DOI: 10.1242/jeb.145268
|View full text |Cite
|
Sign up to set email alerts
|

Feeding through your gills and turning a toxicant into a resource: how the dogfish shark scavenges ammonia from its environment

Abstract: Nitrogen (N) appears to be a limiting dietary resource for elasmobranchs, required not only for protein growth but also for urea-based osmoregulation. Building on recent evidence that the toxicant ammonia can be taken up actively at the gills of the shark and made into the valuable osmolyte urea, we demonstrate that the uptake exhibits classic Michaelis-Menten saturation kinetics with an affinity constant (K m ) of 379 µmol l −1 , resulting in net N retention at environmentally realistic ammonia concentrations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 61 publications
0
8
0
Order By: Relevance
“…Nawata et al (2015) reported that Squalus acanthias are N limited and, when presented with high concentrations of ammonia in the water, they have the ability to scavenge ammonia-N, convert it into urea, and elevate urea-N excretion rates. This uptake of ammonia exhibits classic Michaelis-Menten saturation kinetics, resulting in a net retention of nitrogen (Wood and Giacomin 2016). Along with other transformations at the gill, it is possible that at high temperatures the ammoniaconserving uptake mechanism could have been impaired, leading to the high temperature sensitivity seen.…”
Section: Temperature Effects On Ammonia Excretionmentioning
confidence: 99%
See 2 more Smart Citations
“…Nawata et al (2015) reported that Squalus acanthias are N limited and, when presented with high concentrations of ammonia in the water, they have the ability to scavenge ammonia-N, convert it into urea, and elevate urea-N excretion rates. This uptake of ammonia exhibits classic Michaelis-Menten saturation kinetics, resulting in a net retention of nitrogen (Wood and Giacomin 2016). Along with other transformations at the gill, it is possible that at high temperatures the ammoniaconserving uptake mechanism could have been impaired, leading to the high temperature sensitivity seen.…”
Section: Temperature Effects On Ammonia Excretionmentioning
confidence: 99%
“…Squalus acanthias was chosen as our experimental model due to the extensive body of literature on the physiology of this species, which is a migratory, long-lived, very important demersal resource that is under threat due to overfishing and global climate change (Taylor and Galluci 2009), like many other marine elasmobranchs (Dulvy et al 2014). The present investigation was part of a larger ongoing study on the osmorespiratory compromise and gill function in this species (Zimmer and Wood 2014;Nawata et al 2015;Wood and Giacomin 2016). The osmorespiratory compromise is the functional trade-off between respiratory gas exchange versus osmolyte and water exchange that has been well documented in freshwater teleosts (Randall et al 1972;Nilsson 1986) but never examined in marine elasmobranchs.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…Indeed, Ballantyne (2016) has characterized them as the most nitrogen-limited aquatic vertebrates. Studies using the spiny dogfish shark (Squalus acanthias) as a model system have described the retention and/or scavenging of nitrogen in the gills (Boylan, 1967;Wood et al, 1995;Pärt et al, 1998;Fines et al, 2001;Hill et al, 2004;Wood et al, 2013;Nawata et al, 2015;Wood and Giacomin, 2016), kidney (Kempton, 1953;Forster and Berglund, 1957;Schmidt-Nielsen and Rabinowitz, 1964;Schmidt-Nielsen et al, 1972;Boylan, 1972;Hays et al, 1977;Wood et al, 1995), rectal gland (Burger and Hess, 1960;Zeidel et al, 2005) and gut (Wood et al, 2007b;Anderson et al, 2012;Liew et al, 2013;Anderson et al, 2015). The intestine (also known as the spiral valve in elamobranchs because of its unique structure) appears to be particularly important in this regard.…”
Section: Introductionmentioning
confidence: 99%
“…Based on only one study (Wood et al, 2009) that measured ammonia concentrations (1-3 mmol l −1 ) in gastric chyme (not intestinal chyme) of Squalus acanthias, ammonia levels are only approximately 1% of urea levels. Nevertheless, the gills are capable of scavenging ammonia from even lower concentrations in the external water (Nawata et al, 2015;Wood and Giacomin, 2016), so it seems likely that the intestine would be able to absorb ammonia from the chyme, especially because evidence for carrier-mediated ammonia uptake has recently been presented for the teleost intestine (Rubino et al, 2014;Rubino et al, 2015).…”
Section: Introductionmentioning
confidence: 99%